"The great foes of reality" : attitudes to language in selected novels by Joseph Conrad - McDonald, Peter (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
This dissertation examines Conrad's ambivalent attitude to the value of words in human affairs. Though his critical attitude is the main focus of the argument, his positive attitude will also be considered in some detail. In the first chapter, on The Nigger of the 'Narcissus', the critical attitude is primary. In this story language is seen in relation to silence and action, and in both cases the non- linguistic element is celebrated, while words are censured. Yet the values implied by the tale leave the writer of fiction, and the narrator who emerges at the end of the story, in an uncertain position: the world presented in the novel undermines the mode of presentation which is the novel. This paradox is to some extent resolved in the following two chapters which deal with Conrad's complex response to the culture of European imperialism. Chapter 2, on Heart of Darkness, examines the ways in which words contribute to the systematic lies that sustain the nineteenth-century civilizing mission. The story is, however, not wholly critical of language, since the value of Marlow's spoken narrative is clearly endorsed. Chapter 3 offers a more detailed account of the relationship between the story-teller and his society, and of the value of Marlow's words. In Lord Jim, Marlow's account of Jim is contrasted with the account of him given by the court of inquiry, and with the notion of the hero projected in the romantic fictions which Jim reads. Once again Marlow's use of language is affirmed, while other uses are shown to be reductive, or simply spurious. The final chapter deals with Under Western Eyes. Of the four novels selected for this thesis, Conrad's "Russian novel" offers the most explicit and sustained critique of language. The novel suggests that any simplistic identification of language with "communication" is naive, if not misleading. In the conclusion I discuss Conrad's understanding of the nature and function of his own words, as set out in the preface to The Nigger of the 'Narcissus' and A Personal Record
Keywords: Conrad, Joseph, 1857-1924